Militant Constitutionalism – A Promising Concept to Make Constitutional Backsliding less likely? - Jerg Gutmann; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2019)
Constitutional democracy is in decline and many would-be autocrats try to elude constitutional constraints or even to exploit constitutions in their favor. We make a number of proposals for designing constitutions that are more resilient against such attempts. A first look at the empirical evidence, however, is sobering. There is little evidence that many appealing constitutional rules are able to increase constitutional resilience.
Keywords: H11; K38; P51; 320; constitutional compliance; militant democracy; militant constitutionalism; de jure de facto gap; democratic backsliding